THE TRANSLATION OF MILITARY REGISTER IN THE WAR MOVIE SUBTITLE - Havid Ardi (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2013)
Subtitling is a kind of audiovisual translation/AVT. Translating oral dialogue into text (subtitling) has various aspects that must be considered, such as time exposure, space limitation. Related to sociolinguistic aspect, it is also known that language user and usage determined by various factors, such as, age, sex, and profession. One of the objects in sociolinguistics is register, a language variation, which exists in any social group. This research is aimed at discovering the ways of translator make the subtitle of military register as the character of a social group. Besides, it also aims at finding problems in the subtitle of military register and its implication toward teaching the translation subject. The tentative finding shows that military register tends to be translated in general term and non military register. Keyword: subtitling, military register, audiovisual translation